Therapeutic revolutions pharmaceuticals and social change in the twentieth century - Greene, Jeremy A., 1974-; Condrau, Flurin; Watkins, Elizabeth Siegel (The University of Chicago Press, 2016)
When asked to compare the practice of medicine today to that of a hundred years ago, most people will respond with a story of therapeutic revolution: back then we had few effective remedies, now we have more (and more powerful) tools to fight disease, from antibiotics to psychotropics to steroids to anticancer agents. This collection challenges the historical accuracy of this revolutionary narrative and offers instead a more nuanced account of the process of therapeutic innovation and the relationships between the development of medicines and social change. These assembled histories and ethnographies span three continents and use the lived experiences of physicians and patients, consumers and providers, and marketers and regulators to reveal the tensions between universal claims of therapeutic knowledge and the actual ways they have been used and understood in specific sites, from postwar West Germany pharmacies to twenty-first century Nigerian street markets. By asking us to rethink a story we thought we knew, "Therapeutic Revolutions" offers invaluable insights to historians, anthropologists, and social scientists of medicine.